Reliability of open architecture anchors in biocomposite material: medium term clinical and MRI evaluation. Our experience. - Di Benedetto, Paolo; Lassandro, Nunzio; Beltrame, Alessandro; Mancuso, Francesco; Giardini, Piero; Causero, Araldo (Acta Biomedica Atenei Parmensis, 2020)
Objectives: Comparing radiologic bone ingrowth and the clinical outcomes of an open-construct (PEEK) (polyether ether ketone) suture anchor with those of a bio-composite suture anchor (glycolic polylactic acid anchors, beta-tricalcium phosphate and calcium sulphate) in patients with arthroscopic rotator cuff repair. Methods: From August 2017 to January 2019, 33 patients of both sexes, aged between 44 and 78 years underwent arthroscopic rotator cuff repair for tears considered repairable with an extension not exceeding4 cm. The bioabsorbable anchors used comprised glycolic polylactic acid/beta-tricalcium phosphate/ calcium sulphate, and the non-absorbable anchors in polyetheretherketone (PEEK). All patients underwent MRI evaluation at 12 months postoperatively to determine complications and identify any re-tear. Results: Clinical scores showed an improvement from both clinical and functional point of view. There were no statistically significant changes compared to the physical examination. On radiographs, mobilizations, anchor pull-outs or other complications did not occur in each group. Conclusions: Shoulder function improved after complete repair of the rotator cuff and similar clinical results were achieved regardless of the material and shape of the suture anchor. The bioabsorbable anchors in innovative open architecture material seem to have results comparable to peek anchors. Unfortunately, further studies are needed to define the advantages in using one material compared to the other. (www.actabiomedica.it)